New dress a day : the ultimate DIY guide to creating fashion dos from thrift-store don'ts - Lynch, Marisa (Ballantine Books, 2012)
"Go from thrift-shop cheap to runaway chic each and every day! Based on her wildly popular blog of the same name, guerrilla seamstress Marisa Lynch shows you how to easily (and affordably!) transform your wardrobe from frumpy to fabulous! With just a snip here and a stitch there, your basement bargains will rival anything in designer collections. Yes, with a little imagination--and DIY tools like needles, thread, and safety pins--you too can update an outdated castoff. Inside you'll discover how to ace the sewing basics (remember: safety first!), create DIY designer look-alikes, cut Flashdance-inspired sweatshirts, make an old, tired muumuu a smashing must-have, give bridesmaid dresses a second life, dye your way to a vibrant new wardrobe, whip up accessories in seconds, style the same dress seven different ways. Complete with colorful before-and-after photos, fun sidebars, and even a groovy sewing song playlist to get you in the zone, New dress a day proves that you don't need a sewing machine or a big budget to turn unfashionable trash into stylish treasure"--